The relevance of content in ICT initiatives in Indian agriculture - Glendenning, C.J.; Ficarelli, P.P. (International Food Policy Research Institute, 2012)
In the past decade, many information and communication technology (ICT) projects in Indian agriculture have emerged, either substituting or supporting extension services by providing farmers with access to agricultural information. ICTs have the potential to reach many farmers with timely and accessible content. But the content that the ICTs deliver has more relevance if it is localized and context specific, as this improves the value and actionability of the information, which can have important impacts on farm management. The localization of content is influenced by how the ICT projects access, assess, apply, and deliver content. This paper examines the content development and management processes occurring in six well-known ICT projects in Indian agriculture. There are important lessons to be learned from a case study of this process. Content management and development through ICTs is important to examine because public extension services may be able to increase their efficiency and effectiveness by using these tools to support their work with farmers. Though there are differences in scale and mechanisms of delivery and feedback, all of the case study projects use a network of experts in relevant fields to provide content, though the extent of localization varies. Despite the best efforts of these and many other e-agriculture initiatives in India, there is no easy way for their collective knowledge to be tapped, tracked, and put to use across the different platforms. In fact, there is a critical missing link to bridge the gaps between local or parochial access and serving public needs. To mainstream such ICT efforts and knowledge management in agriculture for rural livelihoods, it is necessary to put in place a centralized search engine, or harvester, to access the decentralized and dispersed digital agricultural information repositories and network of experts.